PENGARUH KOMPETENSI, BUDAYA KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN HOME INDUSTRY KERUPUK SARIPATI SINGKONG DI KABUPATEN GRESIK - jurnalpps pps; Muhammad Syafiuddin; Indra Prasetyo (Jurnal Manajerial Bisnis, 2021)
The purpose of this study was to determine and analyze the effect of competence, work culture and compensation on the performance of home industry employees of cassava crackers simultaneously and partially. To analyze the effect of competence, work culture and compensation on employee performance. The data analysis technique used multiple linear regression analysis. The results showed that simultaneously, all independent variables such as competence, work culture and compensation had a significant effect on employee performance. The influence given by the three independent variables is positive, meaning that the higher the competence, work culture and compensation simultaneously, the higher the employee's performance will be. Partially, the competency variable has no significant effect on employee performance. While the variables of work culture and compensation each have a significant effect on employee performance.